Blown by the same wind - Straley, John, 1953- (Straley, John, 1953- Cold Storage novels., 2022)
"Things in the sleepy fishing town of Cold Storage, Alaska, are changing. It's the summer of 1968; the men are wearing their hair long, the Vietnam War is at its height, and multiple assassinations have gripped the country. But some things remain the same. Ellie's bar is still the place to catch up on the town gossip, and there's a lot to talk about, from the boys who have returned from the war (and the ones who haven't), to the robberies that are plaguing the locals, to the new guy in town: a famous monk from Kentucky. Ellie, herself a fugitive of sorts, is curious about this "Brother Louis," and worries about his motives, but he seems harmless enough. However, when a handful of other outsiders arrive to town and start poking around the bar and asking questions, Ellie begins to have reservations. Have they followed this mysterious monk, rumored to be the famous author Thomas Merton, to Cold Storage? And what is it that they want, particularly the inept FBI agent with the strange name: Boston Corbett? Inspired by assassination conspiracy theories, the life of Thomas Merton, and the changing tide of the '60s, Blown by the Same Wind is a coming-of-age story for the town of Cold Storage as a whole"--